A qualitative investigation of the romantic relationship experiences. of South Korean lesbians in early adulthood - Kim, Eunha; Kim, Haebeen; Lee, Kahee (Psychology and Sexuality, 2022)
Although social acceptance of lesbian women has improved in many countries, they still face great challenges in South Korea. The purpose of this qualitative study was to explore South Korean lesbian younger adults’ perceived challenges related to their romantic relationships and to identify the factors that help them cope. For this, using a convenience sample, we recruited and interviewed 13 South Korean lesbian younger adults attending colleges or graduate schools and analysed their data through consensus qualitative research. Analyses revealed that issues related to family, friends, strangers, and same-sex female coupling; the heteronormative context; and biases against lesbian couples were the major challenges perceived by the participants. In addition, they identified intracouple, interpersonal, and environmental and social factors that helped them cope. Theoretical, practical, and research implications of the findings are discussed.
Keywords: challenges; helpful factor; romantic relationships; sexual orientation; South Korean lesbians